Effect of topical nasal anesthetic on swallowing in healthy adults: A double‐blind, high‐resolution manometry study. (20th November 2017) - Guiu Hernandez, Esther; Gozdzikowska, Kristin; Apperley, Olivia; Huckabee, Maggie‐Lee
Abstract : Objective: Topical nasal anesthetic (TNA) is used when evaluating pharyngeal swallowing with high‐resolution manometry (HRM). It is unclear if desensitizing the nasal mucosa improves procedure tolerability or affects pharyngeal pressure. This study evaluated the effects of TNA on comfort and pharyngeal pressure using HRM. Methods: A double‐blinded study was conducted with 20 healthy participants ( x ¯ = 27 years). Participants performed five saliva and five 10‐mL swallows during two exams with ManoScan HRM ESO catheter (Medtronic, Minneapolis, MN) randomized under placebo (nonanesthetic lubricant) and anesthetized (0.4 mL of 2% viscous lidocaine hydrochloride) conditions. Comfort was rated using a 100‐mm visual analog scale (VAS). Pharyngeal HRM amplitude and timing were analyzed. Results: VAS ratings were similar under placebo (mean = 38.4, standard deviation [SD] = 19.92) and TNA conditions (mean = 33.78, SD = 18.9), with no significant differences between placebo and anesthetized conditions (t[19] = 1.23, P = 0.23) or tolerability at first and second procedure (t[19] = 1.38, P = 0.18). Lower maximum and mean pharyngeal pressure were found for the TNA condition when compared to placebo (dry: maximum [−15.45 mmHg, standard error (SE) = 5.06 mmHg, P = 0.021]; mean [−5.22 mmHg, SE = 1.58 mmHg, P = 0.005]), and (liquid: maximum [−14.79 mmHg, SE = 5.01 mmHg, P = 0.010]; mean [−2.79 mmHg, SE = 1.99 mmHg, P = 0.008]). Conclusion: This double‐blind, randomized study is the first to investigate effects of TNA on tolerability and pharyngeal pressure using HRM. Results indicate TNA offered no significant difference in procedure comfort while affecting the magnitude of pharyngeal swallowing. Level of Evidence: 4. Laryngoscope, 128:1335–1339, 2018